Negara Ditengah Ancaman Demokrasi Siber - Faisyal Faisyal (Oratio Directa (Prodi Ilmu Komunikasi), 2020)
Abstract  This paper aims to illustrate critical about the phenomenon cyber democracy born of information and communication technology. Presence information and communication technology give a new color in national life. Space of interaction in cyber democracy become a tool in channeling political interests. On the other hand, cyber democracy get gave birth to political actors which threatens the country. The political actors interact without regard to democratic conditions, as respect for human rights - to threaten the continuity of democracy.  Keywords: Cyber democracy, digital, new media, conflict.